Hubungan Pola Makan dan Pola Istirahat dengan Kejadian Premenstrual Syndrome - Passe, Rosita; Saleh, Syamsuryanita; Marwang, Sumarni (Poltekkes Kemenkes Kupang, 2024)
Background: The developmental stage in adolescent girls is marked by menstruation, physical and emotional changes often occur before menstruation begins, this condition is usually called Premenstrual Syndrome (PMS). Objective: The aim of this research is to determine the relationship between eating patterns and rest patterns with the incidence of PMS in Level II D.III Midwifery Students at Megarezky University, Makassar. Method: This research uses an analytical observation method with a cross-sectional research approach. The sample used in this research was part of Level II female students, totaling 89 students. This sample collection technique uses probability sampling techniques including stratified random sampling techniques. Data analysis was carried out in SPSS using the Chi-Square statistical test. Results: The results of the research show that there is a relationship between eating habits and rest patterns and the incidence of PMS in Level II midwifery students of the DIII Midwifery Study Program with a p-value for eating habits > (0.003) > α (0.05) and a ρ-value for Rest Pattern (0.004) < α (0.05). It is hoped that the results of this research can deepen female students' understanding of PMS and help them maintain proper eating and resting habits.